Recomendações para o desenvolvimento de cadeiras, a partir de uma análise ergonômica: arremesso do peso nos Jogos Parapanamericanos 2007 - Freire, Gilberto Martins (2008)
The aim of this paper is to create a folder with rules and ergonomic recommendations after analyzing real situations, where it could be observed that the shot put wheelchairs are not compatible with its users. The methodology used was the Work Ergonomic Analyses (AET), according to the model created by Santos e Fialho (1995). In this way it was analyzed the relation between the ergonomic inconveniences of shot put chairs, modus operandi demanded for it and the effects on the disabled athletes performance during the Panamerican Games in Rio de Janeiro 2007. After checking the work reality of shot putting on a wheelchair it became clear that the analyzed chairs were not compatible with its users. It was observed that the ergonomic inconveniences were favorable to a correct body posture, making the disabled athlete have a better performance accordingly to the chair. The use of Work Ergonomic Analyses (AET) in the para sport scene proved to be an important tool to verify the dysfunctions of shot put chairs, becoming one methodological option for the investigation for disabled athletes area. Concluding that, the inconvenient functions of this technological activity, ruled, symbolic and organizational are factors that interfere or even determine health problems, comfort, safety and the athletes’ performance.